Ash aerosol partitioning and ash deposition during the combustion of petroleum coke/natural gas mixtures. (15th November 2019) - Wang, Yueming; Wu, Jianqun; Li, Xiaolong; Yu, Dunxi; Xu, Minghou; Wendt, Jost O.L.
Highlights: Organically associated minerals can be rapidly vaporized to form submicron particles. A coagulation model can be applied to predict the formation of submicron particles. Less alkali metals are present in submicron particles under higher flame temperature. Iron is significantly enriched in generated fouling ash deposits. Abstract: This paper is concerned with the formation of ash aerosols and their subsequent deposition on a heat transfer surface during the combustion of petroleum coke. The subject is of interest for two reasons: first, petroleum coke is a good alternate fuel for power plants, and fouling has been identified as a challenging problem, especially under fuel rich conditions; second, this work sheds light on ash aerosol partitioning and subsequent deposition mechanisms as these relate to the fate of organically bound metals in solid fuels in general. In this work, which did not focus on ignition but on ash transformations and deposition, a 100 kW rated down-fired laboratory combustor was employed and natural gas was co-fired with the coke in order to facilitate ignition. Two conditions were considered: 1) air combustion (denoted as Air); 2) oxy combustion with 70% O2 in the inlet oxidant gas (denoted as OXY70). Experimental data presented here consist of particle size distributions (PSD's), size segregated ash aerosol compositions and information on deposit compositions on a temperature controlled deposit probe. Experimental aerosol size distributions differ between air- and oxy-combustion conditions and are in good agreement with aerosol coagulation theory. The submicron mode in the ash aerosol PSD is proportionately several orders of magnitude greater (on a per kg total ash basis) for petroleum coke than it is for coal. Surprisingly, compositions of the ash deposits are dominated by Fe even though the Fe content in raw petroleum coke ash is low.